Systematic literature review: analisis kemampuan berpikir kritis siswa melalui pembelajaran kontekstual - Sunaryo, Pranestya Rachmaeny; Hutajulu, Masta; Kadarisma, Gida (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
This study aims to find out how effective the use of contextual approaches is to improve students' critical thinking abilities in the transition period as the study intends to detail and conclude the technology that is currently being used as well as the benefits and limitations it has. The SLR stage is grouping data, analyzing and summarizing the data that has been obtained. To develop students’ critical thinking skills, contextual learning is applied that emphasizes the ability to think at a higher level, linking it to everyday life so that students can transfer that knowledge through scientific disciplines, then collect, analyze, and conclude data obtained from some different information and points of view. The research results obtained are as follows: (1) The use of contextual approaches to learning is very effective in improving students’ critical abilities, (2) characteristics of contextual approaches are very effectively used to improve students’ critical thinking abilities, (3) students are not only fixated on one source but many sources can be obtained by students, thus training students’ critical thinking skills.